Thermal characterization of lignocellulosic residue from different sugarcanes - Ricardo Teixeira Ernesto, Vivian Aparecida [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Hojo, Ossamu [UNESP]; Fertonani, Fernando Luís [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer, 2009)
Bagasse samples from four different sugarcane were directly collected as the residues of milling in a processing plant. The samples were dried at 105 A degrees C, compressed to small granules and then their TG/DTA and DSC curves in synthetic air were recorded. Similar thermogravimetric curves were obtained for the different samples and they exhibited four mass loss steps. However, the analysis of the exotherm DSC peaks showed that the oxidation of the organic matter resulted different enthalpy values (Delta H/kJ g(-1)).
Keywords: Sugarcane bagasse; Lignocellulosic residue; Thermal analysis